Phage‐Derived and Aberrant HaloTag Peptides Immobilized on Magnetic Microbeads for Amperometric Biosensing of Serum Autoantibodies and Alzheimer's Disease Diagnosis. Issue 4 (27th July 2021) - Valverde, Alejandro; Montero‐Calle, Ana; Arévalo, Beatriz; San Segundo‐Acosta, Pablo; Serafín, Verónica; Alonso‐Navarro, Miren; Solís‐Fernández, Guillermo; Pingarrón, José M.; Campuzano, Susana; Barderas, Rodrigo
Abstract: An electrochemical biosensing platform for serum autoantibodies (AAbs) detection is reported in this work, exploiting for the first time six Alzheimer's disease (AD)‐specific phage‐derived and frameshift aberrant HaloTag peptides as receptors, immobilized on magnetic microbeads (MBs) surface and captured on disposable electrodes to perform amperometric detection. Operational analytical characteristics and clinical diagnostic ability of the bioplatform were probed in optimized key experimental conditions by analysing serum AAbs of AD patients and healthy subjects. The value of 100 % obtained for AUC, sensitivity, and selectivity from the all peptides combined ROC curve, indicate full AD‐diagnostic capability of the methodology, which was further implemented, as proof of concept, in a POC multiplexing platform to detect the signature in a single test over clinically actionable times (1 h 15 min), opening great promise for the type of diagnosis and AD patients' monitoring follow‐up currently pursued.  Abstract : An electrochemical biosensing platform is reported, which exploits for the first time the use of six phage‐derived and frameshift aberrant HaloTag peptides as receptors immobilized on the surface of magnetic microbeads (MBs), which were captured on disposable electrodes to perform individual or multiplexed amperometry detection for specific serum autoantibodies with full diagnostic capability for Alzheimer's disease.